Effects of Covid-19 in the Restaurant Industry of Kathmandu Valley - Dhungel, Bashu Dev; Lamichhane, Pitmbar (Journal of Nepalese Management and Research, 2022)
This study has been conducted to analyze the effects of COVID lockdown on restaurant business in Koteshwor area of Kathmandu. It has used primary data in order to meet the basic objectives of the research and used simple descriptive analysis as well as correlation analysis. This study has used multi-staged sampling and collected the data from 30 restaurants among the 32% in Mahadevsthan area of Koteshwor-32, Kathmandu. The result conformed that COVID-19 lockdown has had a devastating effect in the business of restaurant industry. There are some positive aspects like the cleanliness and hygiene are more taken care of these days. Furthermore, it has also found out that business of the restaurants was completely closed during the period of lockdown and they were facing loss. Even after the lockdown was lifted, the ratio between sales and profit has been seemed to decrease.